A universal handover authentication protocol for 5G heterogeneous network - Chen, Boming (2018)
Recent increase in the usage of mobile data and demand for high data rate to support wireless internet and multimedia service have driven the motivation to move into the fifth generation (5G) of wireless communication network. It’s believed that the 5G network will adapts heterogeneous network structure, which consists of smaller cells with different technical specifications and service types. One of the challenges brought by 5G heterogeneous network is that as cell size becomes smaller, users are expected to come across the borders of cells of different service more frequently, and handover process will be intensively involved. However, the existing authentication schemes either display certain vulnerability against malicious attacks, or suffer from great delay and computational complexity. Therefore, a fast, secured and reliable handover authentication protocol address the challenge. To achieve fast and reliable authentication between different network, we proposed a universal handover authentication protocol to be used between cellular network and wireless local area network (WLAN). The proposed protocol adapts directauthentication method with authentication server integrated with access point. The proposed protocol is proved to be logical correct with Burrows-Abadi-Needham (BAN) logic. Formal verification using Automated Validation of Internet Security Protocols and Applications (AVISPA) tool shows that the proposed protocol is secure against malicious attacks. Simulation result of the proposed protocol shows that compared to conventional 3G-WLAN integration protocol, the proposed protocol has a better performance in terms of average delay per authentication under attacks.